The job : an American novel - Lewis, Sinclair, 1885-1951 (The Floating Press, 2012)
American writer Sinclair Lewis was interested in the social implications of the aggressive brand of capitalism that began to emerge in the U.S. the early twentieth century. In The Job, he focuses on the rising stature of women in the workforce, detailing the triumphs and travails of a young woman named Una Golden, who discovers that she has an inborn talent for real estate -- and that she must fight against the nearly overwhelming chauvinism in the industry to stake her claim.